Provincial Land Use Planning Initiatives in the Town of Kapuskasing - Saarinen, O. (Urban History Review / Revue d'histoire urbaine, 1981)
Kapuskasing, Ontario warrants special mention in the history of Canadian land use planning. The town first acquired special prominence immediately following World War I when it was the site of the first provincially-planned resource community in Canada. The early layout of the settlement reflected the imprints of both the "city beautiful" and "garden city" movements. After 1958, the resource community then became the focus for an important experiment in urban "fringe" rehabilitation at Brunetville, a suburban area situated just east of the planned Kapuskasing townsite. The author suggests that the role of the Brunetville experiment in helping to change the focus of urban renewal in Canada from redevelopment to rehabilitation has not been fully appreciated.